Turnover of Registered Nurses in Israeli Hospitals: A Secondary Analysis from a National Survey - Toren, Orly; Zelker, Revital; Lipschuetz, Michal; Riba, Shoshana; Reicher, Sima; Nirel, Nurit (International Journal of Translational Research, 2017)
Aim: To assess the extent and directions of internal hospital turnover of registered nurses and to examine the associated factors and stressors. Background: Internal turnover of hospital nurses is mainly horizontal. Occurring on a large scale, it could lead to dropout of skilled personnel, burdening hospitals both financially and in terms of human resources, affecting the quality of care. Methods: A secondary analysis based on data from the national study on "Patterns and trends of the nursing workforce in Israel". A structured telephone interview was conducted of 2,098 hospital nurses (October 2008-February 2009). Results: The rate of internal turnover between hospital departments was 29.7%. The main departments from which nurses moved were medical and surgical. The main departments from which nurses moved were oncology departments, Intensive Care Units, nursing administration. The major work-related stressor concerned salary (59%), two predictors of internal turnover were nurses with children under the age of 18 and academic degree nurses. Conclusions and Implications for Health Policy: Internal turnover rate in Israeli hospitals is moderate, with high rates in medical and surgical departments. It is vital to identify the main factors associated with high turnover rates and implement focused managerial retention strategies and other intervention programs.
Keywords: Obesity; predictive factors; weight loss; fat mass loss; Mediterranean diet; diet attrition.